A Review of Tidal Power Potential in Kenya - Oronyi Ohuru, Aron (Multidisciplinary Journal of Technical University of Mombasa, 2021)
The world is experiencing a dynamic shift in terms of energy production, with nations focusing more on renewable sources of energy. This is because renewable energy sources are eco-friendly, reserves of fossil fuels around the world are getting depleted, and unstable market prices of these fossil fuels. Here in Kenya, the revolution has been felt, especially with heavy investment in geothermal and wind power. Since hydroelectric, geothermal and wind power account for more than 70% of energy consumption in Kenya, it is evident that Kenya is taking strides in the correct direction. However, tidal energy is still left behind in this foray, despite its large potential due to the presence of Kenya’s coastline measuring 640 km long, and most notably, the predictability of this tidal energy. Due to the fact that tidal energy is directly related to the gravitational relationship between the earth and the moon, which is predictable, tidal energy can really help in terms of reduction of pressure and dependence on the hydro power generating seven forks scheme in Kenya. If well synchronized, tidal energy can help alleviate the chronic power rationing that occurs during the dry season in Kenya. By studying work done in other countries, large scale production of electric power from tidal energy can be achieved.